Introduction - Harder, Ebbe; Fjeld, Per Olaf; Mounayar, Michel (Enquiry The ARCC Journal for Architectural Research, 2008)
This issue contains ten papers presented at the 2008 EAAE/ARCC International Conferenceheld in Denmark. The Royal Danish Academy of Fine Arts, School of Architecture, inCopenhagen graciously and superbly hosted the EAAE/ARCC 2008 conference entitled"Changes of Paradigms in the Basic Understanding of Architectural Research. ArchitecturalResearch and the Digital World.” The papers that follow were selected from over fifty presentedat the conference. The moderators of each paper session and members of the conferenceorganizing committee selected these papers for special recognition. These papers werethen blind peer-reviewed and two papers were selected to receive the designation as ‘BestPaper’, one represents the ARCC and one represents the EAAE.Excerpts from the 2008 Conference Introduction